2015
DOI: 10.1002/etc.3160
|View full text |Cite
|
Sign up to set email alerts
|

Maternally transferred dioxin-like compounds can affect the reproductive success of European eel

Abstract: Reported concentrations of dioxin-like compounds accumulated in the European eel (Anguilla anguilla) were used to perform a risk assessment for eel larval survival, taking into account a modeled amplification of tissue concentrations with a factor of 1.33 during spawning migration. The calculated concentrations of dioxin-like compounds finally deposited in the eggs were compared with the internal effect concentrations for survival of early life stages of the European eel; these concentrations, by lack of exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
(78 reference statements)
0
5
0
Order By: Relevance
“…However, our results suggest that the causality between diet and head shape also controls the pollutant accumulation. Anthropogenic influences may thus turn an adaptive trait into a maladaptive one, as the advantage of adapting towards consuming larger and harder preys in the broad-headed yellow eel may ultimately lead to a lower reproduction potential as silver eel, due to increased pollutant accumulation (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our results suggest that the causality between diet and head shape also controls the pollutant accumulation. Anthropogenic influences may thus turn an adaptive trait into a maladaptive one, as the advantage of adapting towards consuming larger and harder preys in the broad-headed yellow eel may ultimately lead to a lower reproduction potential as silver eel, due to increased pollutant accumulation (17).…”
Section: Discussionmentioning
confidence: 99%
“…Even when eels successfully complete the migration, evidence has shown that 17-52% of the original fat reserves, together with its pollutants, are incorporated in the oocytes. This maternal transfer of contaminants to eggs is expected to increase the mortality of larvae, especially when the eels come from highly polluted environments (17). Thus, pollution impacting physiological processes during the European eel's life cycle is thought to be a crucial factor contributing to their decline.…”
Section: Introductionmentioning
confidence: 99%
“…There have been a few cases of direct eel mortalities due to contaminants (Dutil, ; Dutil, Besner, & McCormick, ), but in the majority of cases, the impact is at the sublethal level ranging from tissue damage, stress, effects on osmoregulation, behaviour alteration, hormonal perturbation and genotoxic effects (Couillard et al., ; Geeraerts & Belpaire, ). Contaminants may also be transferred to the offspring resulting in larval malformation (Byer et al., ; Foekema, Kotterman, de Vries, & Murk, ; Rigaud et al., ; Robinet & Feunteun, ). As a fatty fish, eels are particularly sensitive to contamination.…”
Section: Component 2—increased Contamination Load: Contamination Of Ementioning
confidence: 99%
“…This approach is relevant for dioxin‐like compounds, given that the ecotoxicity of these chemicals to aquatic species has been related to the accumulation of these chemicals during exposure and concentrations in tissues (and in eggs specifically), and those tissue residues have been related to effects on survival and other relevant endpoints, that is, tissue residue benchmarks (Foekema et al, 2016 ; Steevens et al, 2005 ; USEPA, 1993 ). The approach requires a toxicity reference value that is based on tissue residues rather than water concentrations.…”
Section: Resultsmentioning
confidence: 99%